PENGARUH PELATIHAN TERHADAP KOMITMEN ORGANISASIONAL DENGAN ORGANISATIONAL BASED SELF-ESTEEM SEBAGAI VARIABEL PEMEDIASI - Adi Indrayanto; Sigit Nugroho (Faculty of Economics and Business Universitas Jenderal Soedirman, 2013)
The research aims to investigate and examine effect of training on employees' organisational based self-esteem, in the context of organisational commitment at privat organization. It is expected that the result of the research will provide an account to human resources management literature with regards to training, organisational based self-esteem, and organizational commitment issue. The research is a survey which attempts to examine and describe the variables using cross-sectional data analysis. Quantitative approach was employed in this research. The research population consists of employees of product retailer organisations. Total number of the respondents are 81 (response rate is 45%). Multiple regression analysis was employed for data analysis purpose. The result shows that organisational based self-esteem has mediating effect on the relationship between training and organisational commitment.